2004
DOI: 10.1016/s1074-7613(04)00109-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of αβ/γδ T Cell Lineage Commitment and Peripheral T Cell Responses by Notch/RBP-J Signaling

Abstract: RBP-J is a key mediator of Notch signaling that regulates a large spectrum of cell fate determinations. To elucidate the functions of Notch signaling in T cell development, we inactivated RBP-J specifically at two stages of T cell development by crossing RBP-J floxed mice with lck-cre or CD4-cre transgenic mice. The loss of RBP-J at an earlier developmental stage resulted in enhanced generation and accelerated emigration of gammadelta T cells, whereas alphabeta T cell development was arrested at the double-neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
297
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(316 citation statements)
references
References 65 publications
19
297
0
Order By: Relevance
“…We previously found that the Notch-Hes1 axis was required for the development of IL-17 + gd T cells in the fetal thymus (15). Similar to the case for RBP-Jk-deficient DN cells (40), conditional deletion of RBP-Jk mediated by Rag-1 promoter-driven Cre recombinase did not eliminate Hes1 expression on gd T cells, suggesting that Notch signaling in the thymus regulated Hes1 expression independently of RBP-Jk. The different signaling pathways explain why Notch signaling can be involved in both the intrathymic development and maintenance of IL-17 + gd T cells.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We previously found that the Notch-Hes1 axis was required for the development of IL-17 + gd T cells in the fetal thymus (15). Similar to the case for RBP-Jk-deficient DN cells (40), conditional deletion of RBP-Jk mediated by Rag-1 promoter-driven Cre recombinase did not eliminate Hes1 expression on gd T cells, suggesting that Notch signaling in the thymus regulated Hes1 expression independently of RBP-Jk. The different signaling pathways explain why Notch signaling can be involved in both the intrathymic development and maintenance of IL-17 + gd T cells.…”
Section: Discussionmentioning
confidence: 70%
“…The different signaling pathways explain why Notch signaling can be involved in both the intrathymic development and maintenance of IL-17 + gd T cells. In contrast to Rag-1-Cre RBP-Jk f/f mice, the number of gd T cells in the thymus of Lck-Cre RBP-Jk f/f mice was not decreased (40). Lck-GFP mice showed that the Lck protein was expressed in late DN2 (also known as DN2b) cells but not early DN2 (also known as DN2a) cells (41,42).…”
Section: Discussionmentioning
confidence: 87%
“…22 Recently, it was also shown that RBP-J-mediated Notch signaling is dispensable for the lineage commitment, survival, and maturation of CD4/CD8 T-cells. 23 In addition, retroviral expression of Deltex1 alone in primary thymocytes and 16610D9 cells was sufficient for the acquisition of resistance to GCs (Figure 6b and c). Therefore, downregulation of the SRG3 expression after positive selection in normal thymocytes is likely to be correlated with the Notch signaling through the Deltex1 activity as well as the TCR signaling.…”
Section: Discussionmentioning
confidence: 92%
“…20,22 Recently, it has been reported that RBP-J deficiency does not significantly perturb the development of DP thymocytes into CD4 and CD8 SP lineages. 23 These results suggest a possibility that Deltex1 may be a major downstream modulator of the Notch signaling pathway controlling the maturation and the GC sensitivity in developing thymocytes.…”
Section: Introductionmentioning
confidence: 87%
“…SOX13, 1 Id3, 2 T-cell receptor (TCR) signal strength, etc. [3][4][5][6][7][8][9][10] However, mechanisms of functional differentiation of effector cd T cells are poorly understood. [11][12][13][14] Key cytokines produced by cd T cells are interferon (IFN)-c, [15][16][17][18][19] tumor-necrosis factor (TNF)-a 20,21 and IL-17, [22][23][24][25][26] and are critical for pathogen clearance, immune regulation and autoimmunity.…”
Section: Developmentmentioning
confidence: 99%